A randomized clinical trial of diabetes self-management for Mexican Americans: Are there serendipitous health benefits for supporters of study participants?. (7th January 2017) - Brown, Sharon A; García, Alexandra A; Orlander, Philip R; Hanis, Craig L
Objectives: Studies of social support in diabetes have focused on the effects of support on the person with type 2 diabetes. We explored diabetes prevention effects of a culturally tailored diabetes self-management intervention in individuals without diabetes who were supporters of intervention participants. Methods: This is a secondary analysis of data from a randomized clinical trial that involved 256 Mexican Americans with diabetes. Each study participant designated a supporter—spouse, relative, friend—who attended intervention sessions and assisted participants in attaining effective diabetes self-management. Supporter's glycosylated hemoglobin (A1C) data were tracked for 1 year to determine diabetes conversion rates in supporters without diabetes at baseline. Results: Fewer individuals in the intervention group (n = 9) converted to an A1C above the 7% threshold, compared to the 1-year wait-listed control group (n = 16). We found a statistically significant difference (p = .021) at 12 months in the number of individuals whose A1C was ⩽8%, with fewer supporters above threshold in the intervention group (reduction of 48%). Supporters in the intervention group with prediabetes, based on baseline A1C, experienced a slight reduction in A1C, while control group supporters with prediabetes experienced an increase. Discussion: The results suggest that there are potential benefits for family members and other supporters of persons with diabetes who participated in diabetes self-management programs.